2021
DOI: 10.1021/acs.est.1c05855
|View full text |Cite
|
Sign up to set email alerts
|

Interface-Enhanced Oxygen Vacancies of CoCuOx Catalysts In Situ Grown on Monolithic Cu Foam for VOC Catalytic Oxidation

Abstract: The development of highly efficient and stable monolithic catalysts is essential for the removal of volatile organic compounds (VOCs). Copper foam (CF) is a potential ideal carrier for monolithic catalysts, but its low surface area is not conducive to dispersion of active species, thus reducing the interface interaction with active species. Herein, a vertically oriented Cu(OH) 2 nanorod was in situ grown on the CF, which acted as the template and precursor to synthesize CoCu-MOF. The optimized catalyst (12CoCu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(61 citation statements)
references
References 60 publications
7
54
0
Order By: Relevance
“…It is found that the Cu(OH) 2 nanorods promoted the interfacial interaction between copper and cobalt, which was conducive to the formation of oxygen vacancies. 78 Similar results were also reported by Wang et al , who synthesized mixed oxide Cu Y Co 3− Y Fe 1 O x using LDHs as the precursor. The catalysts possessed abundant multiphase interfaces for inducing the formation of oxygen vacancies.…”
Section: Construction Strategies For Oxygen Vacancies In Catalystssupporting
confidence: 84%
See 1 more Smart Citation
“…It is found that the Cu(OH) 2 nanorods promoted the interfacial interaction between copper and cobalt, which was conducive to the formation of oxygen vacancies. 78 Similar results were also reported by Wang et al , who synthesized mixed oxide Cu Y Co 3− Y Fe 1 O x using LDHs as the precursor. The catalysts possessed abundant multiphase interfaces for inducing the formation of oxygen vacancies.…”
Section: Construction Strategies For Oxygen Vacancies In Catalystssupporting
confidence: 84%
“…4B, which confirmed the existence of lattice defects. 80 The same phenomenon has been observed in the work of Liu et al 78 Therefore, the defect structure in the material can be reasonably deduced by analyzing whether the XRD characteristic peak widens, weakens, or shifts.…”
Section: Structural Characterization For Oxygen Vacancies In Catalystssupporting
confidence: 67%
“…Interestingly, the staggered Cu–Mn interface can be observed in Cu–Mn/DY, implying that a strong interaction is likely formed between CuOx and MnOx supported on the dealumination Y zeolite (Figure d). The strong interfacial effects can usually induce electron transfer between different media to change the catalytic properties of metal nanoparticles . The EDS elemental maps of Cu–Mn/DY show that Cu and Mn are uniformly distributed on the zeolite support (Figure e), which is consistent with the results of XRD.…”
Section: Results and Discussionsupporting
confidence: 82%
“…The strong interfacial effects can usually induce electron transfer between different media to change the catalytic properties of metal nanoparticles. 39 The EDS elemental maps of Cu−Mn/ DY show that Cu and Mn are uniformly distributed on the zeolite support (Figure 3e), which is consistent with the results of XRD.…”
Section: Structural and Crystal Propertiessupporting
confidence: 84%
“…The electron-gain/loss cycle of Vo has not been specified, but these findings shed light on the key role of Vo in the electronic modulation and electron transfer on catalyst surfaces. By far, the common weakness of using 2D-BiOCl powder catalysts is that the difficult recovery would increase the catalyst cost and cause secondary pollution to the environment, thus preventing the widespread use of 2D-BiOCl for application. , Three-dimensional BiOCl (3D-BiOCl) has a larger specific surface area and abundant vacant sites, which is more conducive to the adsorption of pollutants and electron transport in the Fenton-like process. Thus, it is of great scientific significance and application value to develop a low-cost 3D-BiOCl catalyst for gaseous S-VOC elimination.…”
Section: Introductionmentioning
confidence: 99%